MIRÁNDONOS PARA BUSCAR SENTIDO - Varios, Autores (Tecné, Episteme y Didaxis: TED, 1998)
A first approach of the research is done. The analysis of the Biology teacher’s in formation, characteristics with his/her results, is contributing to the curricular program at the licentiate in Biology. This project tries to be near the imaginative visions that the current students have in relation to emotional, social, educational, political and cultural aspects. The first stage of the research shows the perspective that we have constructed around aspects such as (religion, politics and art), the family, sexuality, expectancy of life, intellectual development, education (pedagogy, research, conceptions about teachers, the teacher’s training and the program itself). The second stage will show what the teachers think about; what we think about them and what the other teachers think and feel. Similarly, a confrontation with theory related to it will be done; finally the achievements will be analyzed in a critical way, and the necessary perspective will be done to construct a curricular project in the Licentiate of Biology.